Statistical Modeling of Dual-Polarized MIMO Land Mobile Satellite Channels - Liolis, K P; Gómez-Vilardebó, J; Casini, E; Pérez-Neira, A I (IEEE transactions on communications, 2010)
This Letter addresses the statistical modeling of dual-polarized MIMO-LMS fading channels. In the absence of accurate experimental results, a statistical model for the characterization of MIMO-LMS channels is proposed based on consolidation of available experimental results for SISO-LMS and MIMO wireless channels as well as on their extrapolation to the MIMO-LMS case of interest. Moreover, a step-by-step methodology for the simulation and time-series generation of the proposed MIMO-LMS channel model is provided, which is useful for the design and performance assessment of MIMO-LMS transmission systems. The proposed model incorporates the effects of all relevant critical channel aspects in a flexible and fully-parameterized way.